Pharmacognostic and Preliminary Phytochemical Investigation on Doronicum scorpioides Roots: Pharmacognosy and phytochemistry of Doronicum scorpioides - Azadeh Hamedi,; Samaneh Rivaz,; Abdolali Mohagheghzadeh, (Iranian Journal of Pharmaceutical Sciences, 2012)
In many herbal markets medicinal plants are sold in dried forms which make it difficult to authenticate them and recognize the adulterations. In the present study the preliminary pharmacognostic parameters including microscopieal studies, extractive values and thin layer chromatography analysis of roots of Doronicum scorpioides (Asteraceae) were evaluated. Three fractions of the plant (hexane, dichloromethane and ethanolic) were applied to the silica gel plates and run in nonpolar, semi polar and polar mobile phases. Chromatographic spots were visualized using different spray reagents. The preliminary screening of the D. scorpioides roots revealed the constituents of the different fractions of the roots including alkaloids, flavonoids, triterpenes saponins, coumarins and essential oils which can be a useful guide for further phytochemical and pharmacognostic research. This is the first report on phytochemical constituents of D. scorpioides roots. Also the pharmacognostic investigation of the D. scorpioides root can be a reliable method for authentication of the medicinal part of the plant and to recognize any adulterations.